Analisis Yuridis Terhadap Praktik Kerjasama Usaha Online Shop Fstore.id di Kelurahan Sukaraja Kecamatan Medan Maimun Kota Medan - Agustina, Maya; Siagian, Nilasari; Nurwandi, Andri (Pusdikra Publishing, 2024)
In the current era of globalization, the continuous development of information and communication technology has resulted in many changes in various sectors. Ease of access to information for various communities has changed the way they interact indirectly. Starting from communication to business transactions and work can be done efficiently without being constrained by distance. The advantage of doing business via the internet lies in the ability to expand marketing reach. In offline businesses, they are usually limited to certain areas in terms of marketing products or services. However, with the help of internet media, anyone can reach a wider global market. FStore.id is an online shop company in Sukaraja Village, Medan Maimun District, Medan City. Initially, this company focused on advertising promotions for fashion products and providing digital marketing services, relying on the marketing capabilities of the business owner. As time goes by, the company expands its business by purchasing products from suppliers on an ongoing basis. Then, the company formed a team and founded FStore.id as a step in developing this business. Finally, FStore.id invited the marketing team to collaborate with the investment system, and the cooperation agreement was regulated in a written agreement document. There are situations where capital owners should not be directly involved in running the company's operations. In practice, there is involvement of capital owners in business operational activities, even though it is not in accordance with the initial agreement in the cooperation agreement. The management is required to follow all instructions given by the investor, even though these are not included in the official agreement. If the manager does not comply with these instructions, the investor has the right to terminate the collaboration without approval. Collaboration between the FStore.id onlineshop business and the owner experienced problems, especially regarding unilateral changes to the contract and unilateral actions on the part of the investor so that the owner of the capital took an action which could be said to violate the agreement to maintain the stability of the company. The main objective of this research is to analyze elements of sharia economic law related to the implementation of syirkah contracts in the Fstore.id online business. This research method uses qualitative research, trying to understand the research object according to the facts in the field without engineering/manipulating the data. The author wants to see how the syirkah contract is applied to the Fstore.id online shop and evaluate its conformity with sharia principles using a combination of Sharia Economic Law and Positive Law.